The Potential Impact of Online/Distance Education for Students with Disabilities in Higher Education: Results from a Meta-Analytic Investigation and Existing Research - Matthew J. Erickson; Karen H. Larwin (International Journal of Evaluation and Research in Education (IJERE), 2016)
The current investigation sought to understand if online and distance course offerings were providing a needed bridge to a post-secondary degree for students with disabilities.  The results of this investigation suggest that there is an absence of empirical research on this topic in the existing published research.  Results presented include findings from the K-12 data examining this impact, and the results from federal investigations on the prevalence of individuals with disabilities attending post-secondary institutions.